2014
DOI: 10.1152/ajpcell.00164.2013
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mononuclear cell angiogenic competency is suppressed by a high-salt diet

Abstract: Autologous bone marrow-derived mononuclear cell (BM-MNC) transplantation is a potential therapy for inducing revascularization in ischemic tissues providing the underlying disease process had not negatively affected BM-MNC function. Previously, we have shown that skeletal muscle angiogenesis induced by electrical stimulation is impaired by a high-salt diet (HSD; 4% NaCl) in Sprague-Dawley (SD) rats. In this study we tested the hypothesis that BM-MNC angiogenic function is impaired by an elevated dietary sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
(66 reference statements)
1
6
0
Order By: Relevance
“…We have previously shown that 7 days of electrical stimulation in vivo produces a robust angiogenic response in rat models that is eliminated by a high salt diet and restored by a low, subpressor dose AngII infusion 7, 21 ; this result was replicated for a control in this study (Figure 1A). In vivo administration of the AT 1 R antagonist Losartan abolished the restorative effect of low dose AngII infusion, whereas Mas1 receptor antagonist A779 had no effect on the ability of low dose AngII infusion to restore angiogenesis.…”
Section: Resultssupporting
confidence: 82%
“…We have previously shown that 7 days of electrical stimulation in vivo produces a robust angiogenic response in rat models that is eliminated by a high salt diet and restored by a low, subpressor dose AngII infusion 7, 21 ; this result was replicated for a control in this study (Figure 1A). In vivo administration of the AT 1 R antagonist Losartan abolished the restorative effect of low dose AngII infusion, whereas Mas1 receptor antagonist A779 had no effect on the ability of low dose AngII infusion to restore angiogenesis.…”
Section: Resultssupporting
confidence: 82%
“…Reports in ischemia disclosed the involvement of bone marrow (BM)-derived mononuclear cells as contributors for angiogenesis, by being incorporated into neocapillaries and by allowing an increased vessel density [51][52][53]. A study from Nolan et al [54] correlated early stages of tumor development with the differentiation potential of BM-derived EPCs and their incorporation into a subset of tumor neovessels.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, adverse effects of BM-derived cells have been described in animal models of diabetes mellitus and arteriosclerosis, 24,25 suggesting a compromised cell graft under translationally relevant conditions of hyperglycemia and hypertension. 26,27 We found almost 30% of the BM MNC being apoptotic before transplantation, a finding that may reflect hypertension-related oxidative stress in the BM. 26,27 In steady state, circulating apoptotic cells were trapped by specialized splenic macrophages in the marginal zone between red and white pulp.…”
Section: Discussionmentioning
confidence: 77%
“…26,27 We found almost 30% of the BM MNC being apoptotic before transplantation, a finding that may reflect hypertension-related oxidative stress in the BM. 26,27 In steady state, circulating apoptotic cells were trapped by specialized splenic macrophages in the marginal zone between red and white pulp. 28 This endogenous scavenging system carefully downregulates immune-stimulatory functions and helps to maintain self-tolerance.…”
Section: Discussionmentioning
confidence: 77%